Today versus Tomorrow : The Sensitivity of the Non-Oil Current Account Balance to Permanent and Current Income - Thomas, Alun (IMF Working Papers; Working Paper, 2009)
This paper applies the Permanent Income Model to the non-oil current accounts of the major oil exporters to assess the extent to which national consumption decisions in these countries are made on the basis of permanent versus current income. A test of whether the return on oil wealth and oil balance coefficients sum to unity is accepted for all specifications that adjust the return on wealth for future population changes. For oil-exporting countries outside Africa, around half of the fluctuations in the private sector non-oil balance are driven by considerations of changes in permanent income (the return on oil wealth) rather than current income. By contrast, for the public sector and African countries permanent income has little or no effect.